Penulisan dan Gender - Hidayat, Rahayu Surtiati (UI Scholars Hub, 2004)
The research aims to describe the differences of language use in the women and men writing. It used the linguistic specific way of collecting and analyzing data from a corpus of Indonesian articles published in the mass media and academic works. The results show that women author used the different Indonesian from men author in syntaxe and choice of conjunctions. These differences are due the way women author and men author were brought up: nurturing the position and the role of each sex.